CHANGES IN ANTIOXIDANT AND PHYSICOCHEMICAL PROPERTIES OF INDONESIAN BLACK RICE FLOUR (VAR. BANJARNEGARA AND BANTUL) DURING NO-DIE EXTRUSION COOKING - Diana Ayu Nindita; Feri Kusnandar; Slamet Budijanto (Jurnal Teknologi dan Industri Pangan, 2018)
This research aimed to evaluate the effect of extrusion cooking conditions (barrel temperature and feed moisture content) on the changes in the physicochemical properties and antioxidant activity of the Indonesian black rice flour (var. Banjarnegara and Bantul). The rice flours were extruded using a no-die twin screw extruder at various barrel temperatures (110 and 140°C) and moisture content of 15, 20, 25% (wb). The total phenolic content (TPC), total anthocyanin content (TAC), and antioxidant activity generally decreased by 29, 46, and 19%, respectively. During extrusion cooking, the higher moisture content re-sulted in a higher retention of anthocyanins hence increased the antioxidant activity as measured by DPPH assay. Increasing temperature produced less retention of both anthocyanins and phenolics, hence lowering the antioxidant activity. The water absorption of the products also increased as the moisture content and barrel temperature increased, while the water solubility of the products became lower as the moisture content increased. Following a no-die extrusion cooking, both varieties of the black rice experienced changes with regard to the physicochemical properties and antioxidant activity. Due to the high antioxidant activity (DPPH value of 510.4 mg Trolox equiv/100 g) and FRAP value of 2340.9 mg Trolox equiv/100 g), the black rice var. Banjarnegara is recommended for further development. No-die extrusion cooking conditions at 110°C and moisture content of more than 25% is selected to achieve fully gelatinized flour with high antioxidant activity.